Christian Vaccine Hesitancy: The Church between Science and State - Stevenson, Austin (Zygon, 2025)
A common feature of the COVID-19 pandemic was Christian leaders using anti-vaccine misinformation to reinforce their opposition to public policy. This illustrates a broader reality: that vaccine hesitancy is not so much a deficit in scientific knowledge as a conflict of values waged through disagreements about vaccine science. Typically, "the science" is a proxy for disputes about justice and democracy. One reason for this may be the contemporary linear model of science-policy interactions, which has operationalized a naively scientistic approach to social issues and frequently circumvented the norms of democratic representation and debate. This has made it easier to position political opponents as enemies of "the science," thereby transforming essential debates about values into intractable disputes about "science." In this article, I consider how political theologies position Christians in relation to allied scientific and governmental institutions, highlighting theological resources that reframe the nature of vaccine debates.